1997
DOI: 10.1016/s1059-1311(97)80003-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pharmacokinetic interaction between remacemide hydrochloride and sodium valproate in epileptic patients

Abstract: A randomized, double-blind, placebo-controlled cross-over study of adjuvant treatment with remacemide hydrochloride was carried out in 17 patients taking sodium valproate (VPA) as monotherapy. Plasma concentration profiles of VPA, remacemide, and its active desglycinyl metabolite (ARL12495XX) were determined following single (300 mg) and multiple dosing (150 or 300 mg twice daily) of remacemide hydrochloride for 14 days with a 300-mg final dose. Central nervous system side-effects were more common at the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…regimen, as adjunctive therapy in refractory patients with epilepsy receiving hepatic enzyme inducing AEDs. Early studies have shown that plasma concentrations of remacemide and the desglycinyl metabolite are reduced in the presence of hepatic enzyme-inducing drugs such as carbamazepine (CBZ) and phenytoin (PHT) 2,3 . In turn, interaction studies have shown that remacemide increases plasma concentrations of CBZ 3 and PHT 4 by inhibiting their metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…regimen, as adjunctive therapy in refractory patients with epilepsy receiving hepatic enzyme inducing AEDs. Early studies have shown that plasma concentrations of remacemide and the desglycinyl metabolite are reduced in the presence of hepatic enzyme-inducing drugs such as carbamazepine (CBZ) and phenytoin (PHT) 2,3 . In turn, interaction studies have shown that remacemide increases plasma concentrations of CBZ 3 and PHT 4 by inhibiting their metabolism.…”
Section: Introductionmentioning
confidence: 99%